METHODOLOGY OF SYSTEMATIC APPROACH TO GUARANTEE THE QUALITY OF TRAINING FOR OFFICERS IN MILITARY UNIVERSITIES - Ryzhykov, V.; Popkov, B.; Horiacheva, K.; Sokolina, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The methodology of systematic approach of guaranteeing the quality of training for military specialists in higher military educational institutions is disclosed in the article. It was determined that the process of education and upbringing takes place under conditions of change of pedagogical goals in any pedagogical system. This process is accompanied by the emergence of new tasks in the field of education and education as society develops. There is a constant updating of scientific information, in the conditions of improvement of existing ones and creation of new methods of teaching and upbringing. There is a constant update of the student and teacher contingent throughout the learning and upbringing process. The systematic approach as a methodological basis for the development of quality assurance systems for the training of military specialists in higher military educational institutions is revealed. It is found that the systematic approach does not exist in the form of a clear methodology with a defined logical concept. This system, formed from a set of logical techniques, methodological rules and principles of theoretical research, thus performs a heuristic function in the general system of scientific knowledge. The functioning of the system is the process of professional training of future military specialists in higher military educational establishments. An important result of the functioning of the system is the high level of readiness of future military specialists for practical activity. This can be achieved by ordering the system based on certain principles. These principles include: the principle of objectivity, completeness, specific-historical (genetic) approach, systematic, contradictory pedagogical experience.